Implementasi Prinsip Syariah pada Pegadaian Syariah (Studi Kasus Cabang Paus, Pekanbaru, Riau) - Anggun Anugrah; Aulia Apriani Jemmi; Fai’qul Halim; Siti Aisyah; Abdul Aziz; Azwar Azwar (AGHNIYA : Jurnal Ekonomi Islam, 2026)
This study aims to analyze the implementation of sharia principles at the Paus Branch of the Sharia Pawnshop. The research method used is a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The results show that the main product of the Sharia Pawnshop is financing based on the rahn contract (Sharia pawn), which provides easy, fast disbursement of funds in accordance with Islamic principles. In addition, there are other products such as arrum, microfinance, and digital gold savings. From the contract aspect, all transactions have fulfilled the pillars and sharia law. From the principle aspect, the Sharia Pawnshop has implemented transparency, fairness and avoided elements of usury, gharar, and maysir. However, challenges remain such as low public literacy and competition with other financial institutions. Overall, the Sharia Pawnshop has carried out its operations in accordance with Sharia principles.